Efecto de abonos orgánicos sobre la actividad microbiológica de los suelos arroceros en la zona de Babahoyo - Limones Contreras, Álvaro Daniel (2021)
This document details the effect of organic fertilizers on the microbiological activity of rice soils in the Babahoyo area. The edaphic microbial processes that largely determine the decomposition of organic matter, depend critically on the structure of the community of microorganisms present. In Ecuador, farmers do not know the proper use for a good fertilization, because they carry it out in a conventional way, visiting a commercial house and buying products that are beneficial to the seller, the farmer being unaware of the existence of organic fertilizers. Among the conclusions, it is determined that the application of organic fertilizers improves the microbial activity of the soils, increasing their fertility; Farmers, in order to obtain a better development of the rice plant, in terms of its growth and development, it is necessary to apply leached organic fertilizers, because its nutritional composition generates greater plant height, reduces the days to flowering, increases the number of ears per plant and therefore greater size thereof, which generates good quality grains and apply organic fertilizers in the correct dose and homogeneous application in rice cultivation in the Babahoyo area, in order to avoid the excessive use of chemical fertilizers that cause damage to the environment.